2021
DOI: 10.1111/ijcp.13994
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effectiveness of a theory‐based intervention to promote diabetes management behaviours among adults with type 2 diabetes in Iran: A randomised control trial

Abstract: Background: Diet and physical activity are recommended for diabetes management.Evidence suggests theory-based interventions are more efficacious than non-theory approaches. This study aimed to test the short-term effectiveness of an integrated theoretical model-based intervention to encourage compliance for low-fat food consumption, carbohydrate counting and physical activity in adults with type 2 diabetes.Methods: A 4-week parallel randomised control trial was conducted in Iran. Data were collected using a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, 28‐30,32‐38 highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, 28‐30,32‐38 highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration.…”
Section: Discussionsupporting
confidence: 90%
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, [28][29][30][32][33][34][35][36][37][38] highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration. Interestingly, we observed that SMBG was independently associated with hypoglycemia in both study populations.…”
Section: Ta B L E 2 Association Between Smbg and Hba1c < 7%supporting
confidence: 90%
“…This finding emphasizes that PBC contributes to the prediction of DSM over and above the effect of intention. Several studies support the finding that PBC is the most critical factor in predicting intent to perform self-management behavior for individuals with T2DM and is also directly related to self-management behavior ( Daryabeygi‐Khotbehsara et al, 2021 ; Gatt & Sammut, 2008 ). In keeping with the present results, a recent study has demonstrated that self-efficacy(similar to PBC) predicts patients’ adherence to DSM recommendations and is particularly significant for overall self-management ( Abubakari et al, 2016 ).…”
Section: Discussionmentioning
confidence: 71%
“…A more extended period of follow-up and intervention targeted at people with a particular health condition may increase the impact of the intervention. The intervention with multiple sessions and evaluation after eight weeks showed a significant effect of intervention and time, though the effect size was not calculated [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…TPB is a theoretical framework proposed by Ajzen and Fishbein containing attitude, subjective norms, perceived behavioural control (PBC), and intention as the constructs for any health behaviour [15]. TPB is used to design various health interventions, including PA promotion among adults, children, and people with different health conditions [16][17][18][19]. Interventions based on this theory were found most effective in increasing PA intention and behaviour than other theories [16,20,21], and an increase in PA was also found [22].…”
Section: Introductionmentioning
confidence: 99%